Estudio comparativo de las aplicaciones móviles híbridas desarrolladas con el lenguaje de programación JavaScript, y las aplicaciones móviles nativas - Valero Avilés, Mildre Valeria (2022)
This study seeks to demonstrate how mobile applications work today, the types of applications that exist, their main platforms and the technologies that are implemented for the development of apps, define the characteristics of each of them, their architecture and the way in which that these take advantage of the capabilities of mobile devices.The way in which mobile applications have become a necessary tool for the development of people's daily activities is analyzed, and the way in which they can fulfill a variety of tasks, each one using their individual characteristics.For the development of this study, descriptive research was implemented and it was designed under the methodological approach of the qualitative approach, as a data collection technique, documentary and bibliographic analysis was used, since the objectives of this study seek to determine the characteristics and functionalities of The different types of applications used these methodologies and techniques that allow us to focus on meeting the objectives